2017
DOI: 10.3382/ps/pew444
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the in vivo digestion of plant proteins in broiler chickens

Abstract: The use of various protein sources (industry by-products, proteaginous) in poultry diets requires a greater understanding of protein digestion mechanisms. The aim of this study was to characterize the molecular actors required for protein digestion in broilers fed 4 different diets containing soybean meal, rapeseed meal, pea, or corn distiller's dried grain with solubles as the only protein source. The digesta of the digestive tract segments were collected and soluble proteins were analyzed by SDS-PAGE. SDS-PA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
(45 reference statements)
0
13
1
Order By: Relevance
“…There were no significant dietary treatments effect (P>0.05) on relative digestive organ weight and length of the intestinal tract at 35 d of age (Table 3 Contrary, Fernandes et al (2013) observed that the inclusion of different sorghum particle size (partially ground or whole grain) in the broiler diets significantly increase gizzard and small intestine weight, which could be explained due to a greater development of the intestinal mucosa (Tarachai and Yamauchi, 2000). The pH in the digestive tract segments is very important in protein digestion as it affects the processing of endogenous proteases into their mature form, but also the solubility of the dietary proteins (Recoules et al, 2017). Our results shown that the value of intestinal digesta pH (Table 3) was similar in broilers fed the WS compared with C diet (P>0.05) and as expected, the pH value increased in the different segments of the digestive tract from 5.59 (duodenum) to 6.56 (caecum).…”
Section: Resultsmentioning
confidence: 99%
“…There were no significant dietary treatments effect (P>0.05) on relative digestive organ weight and length of the intestinal tract at 35 d of age (Table 3 Contrary, Fernandes et al (2013) observed that the inclusion of different sorghum particle size (partially ground or whole grain) in the broiler diets significantly increase gizzard and small intestine weight, which could be explained due to a greater development of the intestinal mucosa (Tarachai and Yamauchi, 2000). The pH in the digestive tract segments is very important in protein digestion as it affects the processing of endogenous proteases into their mature form, but also the solubility of the dietary proteins (Recoules et al, 2017). Our results shown that the value of intestinal digesta pH (Table 3) was similar in broilers fed the WS compared with C diet (P>0.05) and as expected, the pH value increased in the different segments of the digestive tract from 5.59 (duodenum) to 6.56 (caecum).…”
Section: Resultsmentioning
confidence: 99%
“…However, digestion by endogenous protease is incomplete. Recent studies using proteomics approaches have revealed the presence of partially digested proteins from soybean meal (and other legume and cereal feed ingredients) in broiler digesta [2,3]. It is estimated that only about 80% of dietary soybean meal is digested by swine and poultry [4,5] or even less in high fiber, high phytate diets such as those containing industrial by-products [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of these plant proteins with the enzymes secreted by the digestive tract within each segment and not only the ileum, is also very important to better appreciate the dynamics of protein digestion. The catalog of proteins/enzymes that participate in chicken digestive processes is not yet complete, although some recent proteomic approaches on jejunum 6 and ileum 7 allowed the identification of many other proteins in addition to the well-known pepsin, chymotrypsin, trypsinogens and amylase 813 . The activity and function of most of these emerging molecules are still predicted based on homologies with bovine and porcine species, and their secretion by each digestive segment in chicken species have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%